Socioeconomic factors to improve production and marketing of the pecan nut in the Comarca Lagunera - Espinoza Arellano, José de Jesús; Cervantes Vázquez, María Gabriela; Orona Castillo, Ignacio; Molina Morejón, Víctor Manuel; Guerrero Ramos, Liliana Angélica; Fabela Hernández, Adriana Monserrat (Revista Mexicana de Ciencias Agrícolas, 2019)
In the Comarca Lagunera 9 957 ha have been established with pecan walnut, with the region being the third in national importance. The studies of socioeconomic type in walnut in Mexico are mainly descriptive, studies that analyze the relationships between the different variables of the crop that allow making recommendations to boost their growth are required. The objective of this work was to analyze the relationship between various socioeconomic factors such as garden size, training and financing with variables such as yields, price, gross income, infrastructure for harvesting and sale of selected nuts. To obtain the information, a survey was applied during 2014 to a sample of 27 orchards distributed throughout the region. The data were analyzed by Analysis of Variance of a factor to compare the means of the groups: orchards that receive vs those that do not receive training, orchards that receive vs those that do not receive financing; and orchards of up to three hectares vs. more than three hectares. Differences were found in variables such as yields per hectare, price of walnut, sale of selected walnut, infrastructure for commercialization and income. To improve the situation of the walnut orchards in the Comarca Lagunera, it is recommended to strengthen the training and financing, particularly of the small producers and the importance of the size of the orchard, to look for forms of organization to achieve economies of scale in the production and commercialization of the pecan nut in the Comarca Lagunera.